Neuraxial Anesthesia Decreases Post-operative Systemic Infection Risk Compared to General Anesthesia in Knee Arthroplasty - Liu, Jiabin (2013)
BACKGROUND: Surgical stress has been previously shown to result in immune disturbance. Neuraxial anesthesia (NA) has been long hypothesized to blunt undesired surgical insults, and thus limit immune compromise and improve surgical outcomes. We hypothesized that neuraxial anesthesia would decrease postoperative infectious complications compared to general anesthesia among knee arthroplasty patients. METHODS: We studied the American College of Surgeons National Surgical Quality Improvement Program (NSQIP) database from 2005 to 2010. There were total of 16,555 patients included in our final cohort, with 9,167 patients receiving general anesthesia (GA) and 7,388 patients receiving spinal or epidural anesthesia (neuraxial anesthesia). Outcomes of interest included infection-related 30-day postoperative complications, including surgical site related infections, pneumonia, urinary tract infection, sepsis, septic shock, and a composite endpoint of any systemic infection. Multivariable logistic regression was performed to test for effect of anesthesia type while adjusting for the influence of pre-existing comorbidities. RESULTS: The overall mortality was 0.24% and 0.15% among NA and GA subjects respectively (P=0.214). NA subjects had lower unadjusted incidences of pneumonia (P=0.035) and composite systemic infection (P=0.006). After risk adjustment for pre-existing co-morbidities, NA was associated with lower odds of pneumonia (OR=0.51, [95% CI 0.29–0.90]), and lower odds of composite systemic infection (OR=0.77, 95% CI [0.64–0.92]). CONCLUSIONS: Our study suggested that neuraxial anesthesia was associated with lower adjusted odds of both pneumonia and a composite outcome of any systemic infectious complication within 30 days of surgery compared to general anesthesia.